Access/Retention in Multifunctional Resource Rooms: a reality in Amazonas - Dorimar Gomes Ferreira; João Otacílio Libardoni dos Santos (Universidade Federal do Rio Grande do Sul, 2024)
The purpose of this study was to learn about the access and retention of students who are the target audience of Special Education in Multifunctional Resource Rooms (MRRs), from the perspective of teachers, in the municipalities of the Rio Madeira Microregion in southern Amazonas. The Qualitative Descriptive approach was used to outline the research, and data were collected using a semi-structured interview script. The findings point to the role of families, as the school has difficulty sensitizing parents so that they see themselves as an important part of the inclusion process and can recognize the MRR as an important space for their children.